Integrasi Media Audiovisual dalam PBL untuk Meningkatkan Motivasi dan Kemandirian - Dhea Riski Aprilianty; I Gusti Agung Ngurah Trisna Jayantika (Universitas Indraprasta PGRI, 2025)
Student motivation and learning independence remain significant challenges in Indonesian education, as many learners have yet to achieve optimal academic outcomes. This study aims to examine the effectiveness of integrating the Problem-Based Learning (PBL) model with audiovisual media in enhancing students’ motivation and learning independence. The research method used was Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles with 38 students in class XI F at SMAN 3 Denpasar in the even semester of 2024/2025. Data were collected through questionnaires measuring learning motivation and self-regulated learning indicators. The findings reveal a significant improvement in student achievement, with the average score increasing from 67.1 (42% mastery) in the pre-cycle to 74.6 (68%) in cycle I, and reaching 82.3 (87%) in cycle II. Similarly, the average score of learning independence rose from 2.8 (low category) to 3.6 (moderate), and finally to 4.2 (high). These results indicate that the integration of PBL with audiovisual media fosters a more interactive and contextual learning environment, effectively enhancing students’ intrinsic motivation, independence, and academic achievement.